Deprivation amplification revisited; or, is it always true that poorer places have poorer access to resources for healthy diets and physical activity? - Macintyre Sally (International Journal of Behavioral Nutrition and Physical Activity, 2007)
Abstract Background It has commonly been suggested (including by this author) that individual or household deprivation (for example, low income) is amplified by area level deprivation (for example, lack of affordable nutritious food or facilities for physical activity in the neighbourhood). Discussion The idea of deprivation amplification has some intuitive attractiveness and helps divert attention away from purely individual determinants of diet and physical activity, and towards health promoting or health damaging features of the physical and social environment. Such environmental features may be modifiable, and environmental changes may help promote healthier behaviors. However, recent empirical examination of the distribution of facilities and resources shows that location does not always disadvantage poorer neighbourhoods. This suggests that we need: a) to ensure that theories and policies are based on up-to-date empirical evidence on the socio-economic distribution of neighbourhood resources, and b) to engage in further research on the relative importance of, and interactions between, individual and environmental factors in shaping behavior. Summary In this debate paper I suggest that it may not always be true that poorer neighbourhoods are more likely to lack health promoting resources, and to be exposed to more health damaging resources. The spatial distribution of environmental resources by area socioeconomic status may vary between types of resource, countries, and time periods. It may also be that the presence or absence of resources is less important than their quality, their social meaning, or local perceptions of their accessibility and relevance.